Petshop Management Information System - Anjali, Natasha Resya; Rosalpina, Dini; Meidasari, Indah Tri; Vernanda, Dwi; Affandi, Tri Herdiawan (Engineering: Journal of Mechatronics and Education, 2025)
The process of recording transactions and reports on MSME partners that are still carried out manually often causes data input errors, data loss, and difficulties in finding information and also delays in business services, especially for petshop partners. This research aims to design and develop an information system that is able to facilitate faster and more accurate data management, sales transactions, and more quickly and precisely. The method applied in this study is the Agile method, which includes the stages of data collection, system design, implementation, and testing. In the research on pet shop management information systems, the subject is petshops. The results of the research that has been carried out show that this petshop is still carrying out the process of manually entering and managing transaction data. So the implementation of this information system, it is hoped that pet shops can improve services to customers and optimize the management of existing resources. The research also opens up opportunities for further development in system integration with e-commerce platforms to expand market reach